(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
This paper explores the convergence of quantum computing and artificial intelligence (Quantum AI), highlighting how quantum mechanics enables unprecedented computational power through qubits.